Lithotripsy of Urinary Tract Stones by Using Eggshell - Sabar, A. G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
This research aimed to use eggshell powder as a lithtripsian for different types of urinary stones and determine the efficiency of these preparations against different types of stone. The grounded and sterilized eggshell was dissolved in fresh lemon juice .The treatment was orally given for successive 7 days before breakfast. Eighty five patients with different types of urinary stone were participated in this research. All patients were subjected to Ultrasonography and intravenous pyelography examinations to localize the position and detect diameter of the stone. The above examination and also biochemical tests for diagnosis of stones ingredients were repeated after the administration of treatment and excretion of stone fragments in urine. The results cleared out 60 (100% ) of patients with pure uric acid stone undergoes completely lithotripsed of there stones, while 10 out of 25 (40%) of patients with mixed(uric acid/ ca-oxalate) stone were only undergoes lithotripsic events. The results were so promising especially against pure uric acid stone.